Iloli Enterprise: Lorry's maintenance and repair services / Safwan Shahabudin... [et al.] - Shahabudin, Safwan; Abdul Razak, Muhammad Hafiz; Mohd Noor, Abdul Hakim; Ahmad Nazri, Mohammad Afif; Saharun, Zakri Aidil (2016)
Our mission is tor deliver great services beyond industry expectation. Our customer mostly come from key economy industry of Pasir Gudang such manufacturing, logistic, warehousing and other engineering-based industries. These industries require their main transportation which is lorry to perform smoothly in their daily operation.